THE DIFFERENCE OF STUDENT LEARNING OUTCOMES TAUGHT BY GEOGEBRA SOFTWARE ASSISSTED DISCOVERY LEARNING MODEL AND PROBLEM SOLVING LEARNING MODEL ON TRANSFORMATION GEOMETRY - Taihuttu, Sisilia Marselina; Moma, La; Gaspersz, Magy (Jurnal Pendidikan Matematika (JUPITEK), 2021)
This research was conducted with the aim of knowing: (1) student learning outcomes using discovery learning learning models assisted by geogebra software; (2) student learning outcomes taught using problem solving learning models; (3) whether there are differences in student learning outcomes who are taught using discovery learning learning models assisted by geogebra software and problem solving learning models on geometry transformation material in class XI MIA SMA Negeri 5 Ambon. The type of this research is experimental research, using the posttest only control group design. The population in this study were all students of class XI MIA SMA Negeri 5 Ambon with a total of 170 students and the sample in this study was selected using purposive sampling, namely class XI MIA4 with a total of 34 students and class XI MIA5 with a total of 34 students, so the number of samples in this study namely 68 students. The instrument used in this study is a test instrument consisting of description questions for the final test. In this study, statistical analysis was used, namely t-test and the final results of the study were: (1) there were differences in student learning outcomes who were taught using discovery learning learning models assisted by geogebra software and problem solving learning models on geometry transformation material. This is shown in the results of the t-test calculation, namely the value of Sig. (2-tailed) = 0.017 < value of =0.05, thus causing H0 to be rejected and H1 to be accepted. rejected